Intratonsillar abscess: A not-so-rare clinical entity. (April 2019) - Giurintano, Jonathan P.; Kortebein, Sarah; Sebelik, Merry; Thompson, Jerome; McLevy-Bazzanella, Jennifer
Abstract: Objective: To report the prevalence of intratonsillar abscess in the pediatric population at our institution and demonstrate that intratonsillar abscess is a more commonly encountered diagnosis than previously reported. Methods: A retrospective chart review was performed that included patients presenting to our pediatric tertiary referral academic emergency department from January 1, 2014 to December 31, 2014 diagnosed with intratonsillar abscess on computed tomography. Results: In the year 2014, 22 children were diagnosed with intratonsillar abscess by radiological criteria. The majority of patients (82%) required no surgical intervention and were successfully treated with antibiotics and supportive measures. All patients recovered from the infection uneventfully, and there were no treatment complications recorded. Conclusion: Even in recent literature, intratonsillar abscess is described as a rare entity, with few cases reported. In our experience, CT imaging demonstrating the presence of intratonsillar abscess is more common than previously described. Regardless of treatment method, in our experience children with intratonsillar abscess do well clinically.